Implicit reminders of reputation and nature reduce littering more than explicit information on injunctive norms and monetary costs. (December 2022) - Gangl, K.; Walter, A.; Van Lange, P.A.M.
Abstract: The present research addresses tools that could help reduce littering in society. Four interventions were tested which, based on different processes, should reduce littering: monetary information, the depicted injunctive norm, watching eyes and a nature picture. To test these interventions, a randomized controlled trial (RCT) involving 440 community building's waste disposal areas (N = 71, 155) was conducted in Vienna. Littering was assessed before the intervention, 24–48 h after, and again seven weeks after the intervention. Results show that the financial intervention (monetary information) hardly had any effect on littering whereas the norm-based intervention (depicted injunctive norm) led to more littering compared to the control and in particular, the nature picture. In contrast, the reputation-based intervention (watching eyes) and ecology-based intervention (nature picture) reduced littering over time by 4.7%. Thus, interventions based on implicit and soft appeals to reputation and ecology are more effective in fostering clean environments than classical interventions applying explicit information on finances and norms. Highlights: Four interventions to reduce littering were tested in an RCT in the field. Implicit interventions: watching eyes and a nature picture. Explicit interventions: information on financial consequences and injunctive norms. The RCT involved 440 waste disposal areas and lasted for seven weeks. Soft and indirect appeals but not direct information seem to reduce littering.